2003
DOI: 10.1023/b:agen.0000029415.62384.ba
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Granulocytes, in Particular the Neutrophils, Form Important Compartments for Circulating Vascular Endothelial Growth Factor

Abstract: The measurement of circulating vascular endothelial growth factor (VEGF) levels as a prognostic factor will gain increasing relevance in the diagnosis and evaluation of treatment in cancer patients. Angiogenesis is an absolute requirement in tumour growth and metastatic disease. In the present study data are presented which indicate that circulating VEGF mainly resides in peripheral blood cells. In 15 healthy volunteers we demonstrated that approximately 34% of the circulating VEGF resides in platelets and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
348
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(379 citation statements)
references
References 12 publications
9
348
2
7
Order By: Relevance
“…On the other hand, high neutrophil counts in blood causes an increase in vascular endothelial growth factor (VEGF) emission which plays an important role in tumor progression and angiogenesis. Accordingly; increased tumor recurrence, poor prognosis and decreased survival were seen (Kusumanto et al, 2003;Fondevila et al, 2004) For this reason, similar studies have been conducted on NLR in urological malignancies in recent years . It has been found that neutrophilia and lymphocytopenia were associated with poor prognosis in metastatic renal tumors (Ohno et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, high neutrophil counts in blood causes an increase in vascular endothelial growth factor (VEGF) emission which plays an important role in tumor progression and angiogenesis. Accordingly; increased tumor recurrence, poor prognosis and decreased survival were seen (Kusumanto et al, 2003;Fondevila et al, 2004) For this reason, similar studies have been conducted on NLR in urological malignancies in recent years . It has been found that neutrophilia and lymphocytopenia were associated with poor prognosis in metastatic renal tumors (Ohno et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…First, cancer cells release myeloid growth factors (e.g., granulocyte colony-stimulating factor) resulting in production of neutrophils (Lord et al, 1989). Second, circulating neutrophils secrete various cytokines, including vascular DOI:http://dx.doi.org/10.7314/APJCP.2014.15.2.945 Neutrophils and Inflammation Predict Survival in Patients with Advanced Gastric Cancer endothelial growth factor (VEGF), tumor necrosis factor-α, and interleukins, which contribute to the progression of cancer (Ulich et al, 1987;Mahmoud et al, 2002;Kusumanto et al, 2003;Fondevila et al, 2004). Further, we found that elevated neutrophil count was associated with poor pathological differentiation, more advanced stage, more metastatic sites, peritoneal metastasis and higher GPS, all of which are associated with poor prognosis, suggesting that higher neutrophil count was probably related to great tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present research, the absolute neutrophil count was used as a predictor. Furthermore, studies have shown that neutrophils are associated with the systemic release of growth factors and proteolytic enzymes, such as VEGF and matrix metalloproteinase-9, which promote tumor invasion, metastasis and angiogenesis (32,33).…”
Section: Univariate Analysismentioning
confidence: 99%